2007
DOI: 10.1111/j.1365-2672.2007.03306.x
|View full text |Cite
|
Sign up to set email alerts
|

The biodiversity of predominant lactic acid bacteria in dolo and pito wort for the production of sorghum beer

Abstract: Aim: To quantify and identify the predominant lactic acid bacteria (LAB) in dolo and pito wort processing, and to examine their biodiversity at strain level. Materials and Results:The processing of dolo and pito wort was studied at four production sites in Burkina Faso and Ghana. The succession of dominant micro-organisms, pH and titratable acidity were determined from sorghum malt through mashing and acidification to final wort. In the sorghum malt and during mashing, the LAB counts were 5AE7-7AE5 log CFU g )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 43 publications
(92 reference statements)
3
67
1
Order By: Relevance
“…In this context, there is a growing demand for new and improved sorghum beer yeast strains to obtain beers with constant organoleptic characteristics. This demand could be met by non-Saccharomyces sorghum beer yeasts, which are described as fermentations improvers and producers of concentrations of fermentation metabolites of brewing importance [4,7,15,16]. A wide range of volatile compounds was detected in the sorghum beer samples, including six esters, four higher alcohols, six acids and one fatty acid (Figure 2).…”
Section: Volatile Compounds Of the Beersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, there is a growing demand for new and improved sorghum beer yeast strains to obtain beers with constant organoleptic characteristics. This demand could be met by non-Saccharomyces sorghum beer yeasts, which are described as fermentations improvers and producers of concentrations of fermentation metabolites of brewing importance [4,7,15,16]. A wide range of volatile compounds was detected in the sorghum beer samples, including six esters, four higher alcohols, six acids and one fatty acid (Figure 2).…”
Section: Volatile Compounds Of the Beersmentioning
confidence: 99%
“…Various investigations on the use of starter culture for sorghum beer production have been done [15][16][17][18]. Beers obtained from inoculation tests with these starters showed organoleptic and sensory characteristics comparable to beers produced in the traditional way.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from Saccharomyces cerevisiae, the bacterial isolates from the pito samples can be considered microbial contaminants even though the quantities were within the acceptable limits. In a similar study, lactic acid bacteria isolates were found to be involved in the various production stages of Pito [29]. Staphylococcus aureus is a normal flora of the skin, and the common ethological agent of septic arthritis [30].…”
Section: Discussionmentioning
confidence: 93%
“…For solid samples, 10 g of product were mixed with 20 ml of distilled water prior to pH measurement. For liquid samples, the pH was measured directly (Sawadogo-Lingani et al, 2007). The temperature at the beginning and at the end of fermentation was measured with a thermometer (Rweger V104, Swiss).…”
Section: Physico-chemical Analysesmentioning
confidence: 99%
“…The microbiota of many African traditional fermented cereal products have been investigated, e.g. maize based products like kenkey (Halm et al, 1993;Olasupo et al, 1997;Hayford et al, 1999), mawè (Hounhouigan et al, 1993a(Hounhouigan et al, ,b, 1994 and ogi (Johansson et al, 1995;Olasupo et al, 1997), sorghum based product like kisra (Hamad et al, 1992) and dolo (Sawadogo-Lingani et al, 2007), millet based products like kunu-zaki (Olasupo et al, 1997) and bensaalga (Tou et al, 2006). However, only a few studies have been done to date on zoom-koom (Barro et al, 2007;Soma, 2014) and its fermentation process and no information is available on the kinds of micro-organisms involved in the spontaneous fermentation of the dough.…”
Section: Introductionmentioning
confidence: 99%